Open field cultivation of Gerbera fetches more return - Keditsu, Rokolhuii (Indian Horticulture, 2019)
Gerbera is one of the important commercial cut flowers which is in great demand in domestic as well as international market. It holds equally good promise in a wide range of soil and climate, therefore, warrant a splendid future if varieties and growing techniques are well adopted to the given agropedological conditions. Under open field conditions, seasonal influence on growth and flower yield of gerbera provides a greater flexibility in modulating the growing conditions to harness towards better vegetative growth and flower yield. There is an increasing magnitude of vegetative growth, floral response, flower quality, ray floret and disc floret characteristics, contributing towards flower yield during June (March-May) after planting. After this period, there is a decline in vegetative growth which was observed during June, July and August, with a steep reduction in July. The recommended soil and climate analogues would be pathbreaking for growing gerbera in northeast India under open field conditions.